Covered Balloon-Expanding Stents in Airway Stenosis. Issue 2 (April 2017) - Majid, Adnan; Kheir, Fayez; Chung, Jey; Alape, Daniel; Husta, Bryan; Oh, Scott; Folch, Erik
Abstract : Background: The balloon-expanding stents are widely available but rarely described for use within the tracheobronchial tree. This report describes our experience with these stents in airway stenosis particularly as a lobar salvage therapy. Methods: This was a retrospective review of all records in which the balloon-expanding stents were used at a tertiary medical center. Ages, sex, location of stenosis, etiology of stenosis, stent size, duration of stent placement and associated interventions for airway stenosis were recorded. Patient's self-reported respiratory symptoms, dyspnea scale, and radiographic imaging at baseline and after stent placement were also reported. Results: Twenty-one Atrium iCAST stents were inserted in 18 patients with malignant and benign airway disease. The median age was 69.5 years (interquartile range, 53.5 to 74). Most stents (n=20, 95%) were deployed in the lobar airways. There was a significant improvement in the modified Medical Research Council dyspnea scale from median of 3 to 2 ( P <0.05). Self-reported respiratory symptoms improved in 14 patients (78%, P <0.05). Radiographic improvement post Atrium iCAST stent placement was achieved in 15 patients (83%). No deaths were related to airway stenting complications. Adverse events related to stents included migration (n=2, 9.5%), granulation tissue formation (n=2, 9.5%) and mucus plugging (n=1, 4.8%). Conclusions: Lobar stenting with balloon-expanding metallic stents appears feasible, safe and improves symptoms as well as radiographic atelectasis in patients with lobar airway stenosis in this small case series. Larger studies are needed to confirm this observation and to address long-term safety.